A Numerical Study of Forced Convection Heat Transfer Over a Series of Flat Tubes Between Parallel Plates - Tahseen, Tahseen Ahmad (Faculty Mechanical Engineering, UMP, 2012)
This paper presents the numerical study of the two-dimensional forced convection heat transfer across three in-line flat tubes confined in a channel the flow under incompressible, steady-state conditions. This system is solved in the body fitted coordinates (BFC) using the finite volume method (FVM). The constant temperature is imposed on the surface of the tubes as the thermal boundary conditions. The range of the longitudinal pitch-to-diameter ratio SL/Ds is considered of 2.0-4.0 and Reynolds numbers varies within the range of 25-300, and Prandtl number is taken as 0.7. The temperature contours, local Nusselt number distributions at the tube surface and mean Nusselt number were analyzed. The strength of the heat transfer between the surface of the tubes and the air flow increases with increasing Reynolds number and increasing pitch-to-diameter the ratio.